The Construction of National Identity through the Production of Ritual and Spectacle: An Analysis of National Day Parades in Singapore - Kong, Lily (Institutional Knowledge at Singapore Management University, 1997)
In this paper, we adopt the view that 'nation' and 'national identity' are social constructions, created to serve ideological ends. We discuss this in the specific empirical context of Singapore's National Day parades. By drawing on officially produced souvenir programmes and magazines, newspaper reports, and interviews with participants and spectators, we analyse the parades between 1965 and 1994, showing how, as an annual ritual and landscape spectacle, the parades succeed to a large extent in creating a sense of awe, wonderment and admiration. Discussion focuses on four aspects of the celebrations: the site of the parades, their display and theatricality, the composition and involvement of parade participants, and parade themes. We also discuss some examples of alternative readings of parade meanings, illustrating how ideological hegemony is not total.